Non-Linguistic Problems in Arabic Language Learning at Madrasah Aliyah in Kotamobagu City - A. Manangin, Abdul Rahim; Hairuddin, Hairuddin; Hj. Bahri, Ratni Bt. (Yayasan Daarul Qimmah Gorontalo, 2023)
This study aims to: (1) Know what are the nonlinguistic problems faced by teachers in learning Arabic at MA Se Kota Kotamobagu. (2) What are the nonlinguistic problems faced by students in learning Arabic at MA Se Kota Kotamobagu. In this study, researchers used qualitative methods using descriptive qualitative research designs. Data sources from this study are primary and secondary data, as well as data collection techniques used in the form of interviews, observations, and documentation. The results of this study are: (1) Nonlinguistic problems faced by teachers in Arabic language learning at Madrasah Aliyah Se Kota Kotamobagu, namely, lack of teacher competence in carrying out the learning process, changes or changes in curriculum, lack of time allocation, and lack of availability of infrastructure facilities in supporting Arabic language learning. (2) Nonlinguistic problems faced by students in learning Arabic at Madrasah Aliyahh Se Kota Kotamobagu are, low motivation, which is influenced by improper management of learning time, as well as different and fariative educational backgrounds, which causes these students to have difficulty in understanding and receiving Arabic learning materials